Humanity Aspect in Movie of The Captain, Directed by Andrew Lau - ARFANI, SRI (International Journal of English Language and Pedagogy, 2023)
The object of this research is to find out about the humanity aspect in the film The Captain. Humanity it means the nature and characteristics of humans as creatures of high dignity. Humanity describes the expression of the nature and nature that should be possessed by a creature called human. The purpose of this study is to describe the values of humanity towards fellow human beings. This study uses a qualitative method. Then humanity is divided into several types: cooperation, courage, responsibility, perseverance, hard work. In this study, it is hoped that literary works can be studied more broadly in the study of human values and can help further researchers to analyze more about literary works in terms of humanity, both in terms of education, social and culture.